Short-Term Mortality after First Epileptic Seizure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The short-term mortality in a prospective study of a cohort of 804 patients, aged 2 months to 94 years, with a first seizure was determined at the University Hospitals of Bordeaux and Montpellier, France.